A Rare Case of Tracheal Schwannoma Successfully Treated With Endoscopic Resection and Cryoablation Under Rigid Bronchoscopy - Ming Chiu Chan; Cheuk Cheung Derek Leung; Yu Hong Chan; Man Ying Ho; Chun Hoi Chen; Ching Man Ngai; Hiu Ching Christy Chan; Yiu Cheong Yeung (Case Reports in Pulmonology)
We present a rare case of tracheal schwannoma, the first reported in Hong Kong, emphasizing the diagnostic challenges and treatment outcomes. A 54-year-old woman with respiratory symptoms underwent evaluations revealing a tracheal mass causing luminal narrowing. Emergency operation with rigid bronchoscopy and cryoablation successfully removed the tumor. Follow-up bronchoscopies showed a gradual reduction in residual tumor size, with no evidence of recurrence after 3.5 years postoperation. Tracheal schwannomas are exceedingly rare, often resulting in delayed diagnosis. Clinicians should maintain a high suspicion of tracheal tumors in patients with unexplained respiratory symptoms. Spirometry and flow volume loop analysis aid in identifying upper airway obstruction. Rigid bronchoscopy is preferred for diagnosis and treatment, ensuring airway stability and obtaining tissue samples. Surgical resection remains the mainstay, but observation after endoscopic resection may be considered. This case highlights the successful management of tracheal schwannoma through endoscopic resection and cryoablation, emphasizing the need for further studies and case reports on this rare entity.